Public Interest as a Ground for Restriction of the Ownership Right - KIRILLOVA, Elena Anatolyevna; BOGDAN, Varvara Vladimirovna; FILIPPOV, Petr Martynovich; BIDOVA, Bela Bertovna; FILIPENKOVA, Olesya Genadyevna (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017, 2017)
The public interest right as a ground for restriction of the ownership right is studied in this article. The notion of sustainable development, widely discussed in recent years at the international level, considers the thesis of balanced regulation of economic relations as one of the main principles of state policy. The balanced regulation of economic relations is impossible without clear definition of the areas of private and public interests in law, as well as without development of the common approaches to the notion, content, criteria, and principles of restriction of the ownership rights. The purpose of this study is to analyze public interest as a groundfor restriction of the ownership right. This scientific work is based on the dialectical method, in which each legal phenomenon is considered in development, in constant movement, and the contradictions of different levels within the framework of the common system are recognized as the internal impulses of development. The principle of systematic analysis of the limits of implementation and restrictions of private and public ownership rights is actively applied. The study proposes to expand the subject composition in legal relations on restriction of the ownership rights and to introduce a new subject of law (the ʽfuture generationsʽ), the interests of which may become the limit of the implementation of the ownership right; the authors' definition of the ʽinterest of the societyʽ is given, the conclusion is madethat the restrictions of the ownership rights are independent legal relationships, arising from the legal facts, based on the law. The proposal is substantiated that in the system of fundamental human rights and freedoms it is necessary to single out the right to property as the basic right of an individual (person), different from the ownership right. The right to property is a potential, yet unrealized opportunity for everyone to possess any property. The conclusions and proposals made in the study will make it possible to ensure the balance of the property interests of the owners and the society.